Asian development outlook (ADO) 2019 strengthening disaster resilience. (Asian Development Outlook, 2019)
As oil prices rose and Asian currencies depreciated, inflation edged up last year but remained low by historical standards. In light of stable commodity prices, inflation is anticipated to remain subdued at 2.5% in both 2019 and 2020.Risks remain tilted to the downside. A drawn-out or deteriorating trade conflict between the People Republic of China and the United States could undermine investment and growth in developing Asia. With various uncertainties stemming from US fiscal policy and a possible disorderly Brexit, growth in the advanced economies could turn out slower than expected, undermining the outlook for the People Republic of China and other economies in the region. Though abrupt increases in US interest rates appear to have ceased for the time being, policy makers must remain vigilant in these uncertain times.